Structural parameters to consider in selecting silica supports for polyethylenimine based CO2 solid adsorbents. Importance of pore size. (July 2018) - Zhang, Hang; Goeppert, Alain; Kar, Sayan; Prakash, G.K. Surya
Graphical abstract: Highlights: Easily prepared PEI/silica hybrid CO2 adsorbents. Granular silica with pore diameter higher than 240 Å are better for CO2 adsorbents. Changes in the support's surface area had little effect on CO2 adsorption. Adsorption capacity largely dependent on pore diameter. Abstract: Hybrid solid CO2 adsorbents prepared from commercially available silica and polyethylenimine (PEI) are potential candidate for large scale carbon capture applications. In this study, the effect of the silica support structure and morphology on the CO2 adsorption capacity of the adsorbent was investigated. Two series of silica supports with distinct morphology, i.e. granular and microspherical, available from PQ-Corp., and well defined surface area, pore diameter, and pore volume were loaded with branched PEI. The CO2 adsorption characteristics of these adsorbents were measured using thermogravimetric analysis (TGA). The increase in PEI loading on the porous silica caused a significant decrease in surface area and pore volume. At a certain loading level, the pores were completely filled with PEI, and the CO2 diffusion was hindered resulting in lower adsorption capacity and amine efficiency. With granular silicas, supports having an average pore diameter greater than about 240 Å performed best. However, once this threshold in pore diameter was passed, the adsorption capacity did not improve much further. For microspherical silica supports this threshold was around 300 Å. For supports with a same pore volume, the ones with a larger pore diameter had higher CO2 adsorption capacity, even if their surface area was lower. This difference was mainly due to the easier diffusion of CO2 into the pores, because the phenomenon was more pronounced at a low adsorption temperature (25 °C), where diffusion control was most significant.